2012
DOI: 10.1017/s1833367200001061
|View full text |Cite
|
Sign up to set email alerts
|

The role of life friendly policies on employees' work-life balance

Abstract: An employee's inability to balance work and non-work related responsibilities has resulted in an increase in stress related illnesses. Historically, research into the relationship between work and non-work has primarily focused on work/family conflict, predominately investigating the impact of this conflict on parents, usually mothers. To date research has not sufficiently examined the management practices that enable all ‘individuals’ to achieve a ‘balance’ between work and life. This study explores the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Hayman () concluded that employees display higher levels of work‐life balance when operating under flexitime work schedules but found no similar positive outcomes for those operating under flexible work schedules (flexiplace and job share). Along the same lines, Yuile et al () report employees’ self‐reported perception of work‐life balance as positively associated with the availability of flexible work schedules but negatively associated with offsite working arrangements; finally, they report no significant association between carers’ arrangements and perceived work‐life balance.…”
Section: Adapting the Self‐perception Accuracy Model To Work‐life Balmentioning
confidence: 98%
See 3 more Smart Citations
“…Hayman () concluded that employees display higher levels of work‐life balance when operating under flexitime work schedules but found no similar positive outcomes for those operating under flexible work schedules (flexiplace and job share). Along the same lines, Yuile et al () report employees’ self‐reported perception of work‐life balance as positively associated with the availability of flexible work schedules but negatively associated with offsite working arrangements; finally, they report no significant association between carers’ arrangements and perceived work‐life balance.…”
Section: Adapting the Self‐perception Accuracy Model To Work‐life Balmentioning
confidence: 98%
“…Numerous HR practices may be implemented within organizations to address concerns for managing one's multiple roles in life. For expediency, researchers tend to group them into broad categories and, while these vary, practices most commonly associated with a balanced lifestyle include flexible work options, options for reduced hours of work, family‐related leave, and other services such as dependent care and domestic support services (Bloom, Kretschmer, & Van Reenen, ; Dallimore & Mickel, ; De Cieri et al, ; Gregory & Milner, ; Lewis & Smithson, ; Yuile et al, ). Given the potential of these HR practices to support individuals in managing their work and nonwork responsibilities, they are generally viewed as quite beneficial for employees and organizations alike (Aryee et al, ; Beauregard & Henry, ).…”
Section: Adapting the Self‐perception Accuracy Model To Work‐life Balmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies corroborate the importance considering religion, as religious involvement may be an underlying element in explaining how Australian Muslim workers organise meaning to and experience work and nonwork roles. From a workplace management perspective, workplaces cannot ignore how WLC manifests among Australian Muslim workers because there is clear evidence it can result in negative consequences such as job dissatisfaction, absenteeism and staff turnover (Yuile et al, 2012). If workplaces are going to implement policies and strategies to mitigate the negative impact of WLC, it is important to know what form of conflict Muslim workers are experiencing and why.…”
Section: Introductionmentioning
confidence: 99%